Experiences with academic writing: A longitudinal study with diverse students - Ávila Reyes, Natalia; Figueroa, Javiera; Calle-Arango, Lina; Morales, Solange (Education Policy Analysis Archives, 2021)
Writing research in higher education has focused on student’s texts features, but less so on their experiences as subjects who encounter and gradually acquire disciplinary writing. This article seeks to identify factors that shape the development of students’ academic writing during the first undergraduate years and the changes they experience. For three years, 21 students admitted through regular and inclusive admissions to a selective Chilean university were followed. A total of 119 interviews were conducted and qualitatively analyzed to identify themes and compare them between participants, as well as longitudinally. Results show that not enough preparation and orientation about writing hinder participants’ writing development, whereas other people’s guidance play a key role in their learning processes. Furthermore, university writing courses help in learning to write, but there is limited transfer to disciplinary courses.